Growth and lipid profiles of the Antarctic snow microalga Chlamydomonas sp. In response to changes in temperature, photoperiod, salinity and substrate - Cid-Agüero, Pedro; Cuello, Joel L.; Ruiz, Sebastian; Sanchez, Gloria (My University, 2017)
Abstract: The main objective of this study was to investigate culture substrates, stress conditions and cold-adaptive cellular lipid products of potential industrial interest associated with the short-term environmental adaptation by an Antarctic snow microalga. Viable culture lines of the Antarctic snow microalga Chlamydomonas sp. (DPA-02 strain) were obtained after two years storage period at -4 oC without light source. The dark- adapted Chlamydomonas sp. exhibited high sensitivity to light, growing optimally on Bristol media under a light level of 10 μmol m-2 s-1 and a temperature of 12 ± 2°C. The snow microalga yielded 93% of its lipid content as saturated fatty acids, 67% of which was palmitic acid (C16:0). The study also showed the significant alteration of the microalga's lipid profile by modifying the culture's growing conditions, resulting in a significant increase in PUFA's independently of the culture temperature, from about 10% to 70%, when the culture was subjected to continuous darkness over a one-month period. The growth rate of the microalga decreased with increase in NaCl concentration in the growing medium. Further, the microalga was found to be sensitive to the physical matrix on which it grew, showing a higher mortality rate when exposed to a low-temperature shock on a solid medium different than snow or ice. These results provided unprecedented insights into cryoprotective strategies employed by snow microalgae to survive under the severe environmental conditions of Antarctica.
Perfiles de lípidos y crecimiento de la microalga antártica Chlamydomonas sp. En respuesta a los cambios de temperatura, fotoperiodo, salinidad y sustrato
Keywords: snow microalgae; lipids content; cold adaptation; cryoprotectant; photoperiod